A Delicate Equilibrium : Debt Relief and Default Penalties in an International Context. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
Debt relief and penalties are discussed in connection with sovereign-country loans. We focus on conditions for the existence of penalties that are too low for ensuring Pareto efficiency, and show the possible time inconsistency of optimal debt contracts. A methodology for ascertaining debt relief implicit in international loans is outlined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet